Knowledge and attitudes about adolescent pregnancy and contraception postpartum. - Vereau, Dorina (2015)
Descriptive study during two months in 1993 to determine information and attitudes about pregnancy and contraceptives in adolescents girls in the post partum period. Eighty adolescents were surveyed with a closed questionaire 68% had not planned her pregnancy, only 41% were happy and the rest were  indifferent or rejected such pregnancy. Five girls bad tried to interrupt their pregnancy. Eighty-two percent had prenatal control only 23% at Maria Auxiliadora Hospital. Other 23% had had information about contraceptives. Following information post partum, 70% decided to use contraception, mainly IUD. Me conclude it is necessary to reinforce educational activities on family planning during prenatal and postpartum controls.